2023
DOI: 10.1371/journal.ppat.1011165
|View full text |Cite
|
Sign up to set email alerts
|

Berberine governs NOTCH3/AKT signaling to enrich lung-resident memory T cells during tuberculosis

Abstract: Stimulation of naïve T cells during primary infection or vaccination drives the differentiation and expansion of effector and memory T cells that mediate immediate and long-term protection. Despite self-reliant rescue from infection, BCG vaccination, and treatment, long-term memory is rarely established against Mycobacterium tuberculosis (M.tb) resulting in recurrent tuberculosis (TB). Here, we show that berberine (BBR) enhances innate defense mechanisms against M.tb and stimulates the differentiation of Th1/T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…The antioxidant properties and anti-inflammatory effects of berberine cause a decrease in the negative symptoms in neuropathic patients (36,37). Studies have shown that berberine has also a potent effect on lung damage and other pulmonary inflammations (38)(39)(40). Furthermore, berberine has been shown to have antiviral effects against viruses such as herpes simplex, human cytomegalovirus, and influenza A (41)(42)(43).…”
Section: Resultsmentioning
confidence: 99%
“…The antioxidant properties and anti-inflammatory effects of berberine cause a decrease in the negative symptoms in neuropathic patients (36,37). Studies have shown that berberine has also a potent effect on lung damage and other pulmonary inflammations (38)(39)(40). Furthermore, berberine has been shown to have antiviral effects against viruses such as herpes simplex, human cytomegalovirus, and influenza A (41)(42)(43).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we evaluated the potential of BPM in modulating T cell memory responses to mediate long-term memory against M.tb . Recently we and others have shown how antimycobacterial compounds elicit M.tb specific long-term immunity ( 50 52 ). Here, again, we observed that BPM boosted the memory responses in both the lung and the spleen of infected animals.…”
Section: Discussionmentioning
confidence: 99%
“…This is further complemented by adjunct therapy with BCG as well as DOTS therapy, that results in higher T scm responses that further give rise to different memory pools and effector T cells (77, 78). Similarly, whole proteomics analysis of Purified protein derivative (PPD +) healthy individuals when treated with an immunomodulator, Berberine, showed upregulation of glycolytic pathway along with NOTCH3, that may possibly play role in prompting protective T cell effector function against TB (79).…”
Section: T Cellsmentioning
confidence: 99%